Biosensing for food chemistry using graphene based materials as electrochemical platform - Tian, Huidi (2016)
Graphene-based materials have captured considerable attention over the recent years due to their excellent electronical, electrochemical, optical, mechanical and thermal properties. Since their excellent conductivitiy and fast heterogeneous electron transfer (HET) rate, graphene materials have been widely used in electrochemical studies. In this thesis, different chemically modified graphene materials, obtained by several synthetic routes as well as doped by different heteroatoms were used as platforms to improve the electroanalytical detection of various analytes which are correlated to food quality and safety, such as mycotoxins, sugars and DNA nucleobases. The analytical performance provided by the different graphene materials employed in the study was discussed and explained in terms of dopant type, surface area, D/G ratio, and C/O ratio of the materials, and the structure of the analyte was also taken into account. The electroanalytical parameters such as of sensitivity, selectivity, and linearity of response, as well as repeatability of results and limits of detection obtained with the different graphene materials were also compared and discussed.